2017
DOI: 10.1186/s12978-017-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV status and treatment influence on fertility desires among women newly becoming eligible for antiretroviral therapy in western Kenya: insights from a qualitative study

Abstract: BackgroundFactors influencing fertility desires among HIV-infected individuals remain poorly understood. With new recommendations for universal HIV treatment and increasing antiretroviral therapy (ART) access, we sought to evaluate how access to early ART influences fertility desires among HIV-infected ART-naïve women.MethodsSemi-structured in-depth interviews were conducted with a select subgroup of 20 HIV-infected ART-naïve women attending one of 13 HIV facilities in western Kenya between July and August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
3
14
1
Order By: Relevance
“…Childbearing is considered to have great importance in most parts of Africa and being motherhood elevated social status [21][22][23]. In this study of 397 women of reproductive age, ART users in Gondar city administration have participated, we found that the proportion of fertility desire was 55.2%( 95%CI, 50.4, 60.2).Our finding in line with the fertility desire reported in Addis Ababa (54.6%) and…”
Section: Discussionsupporting
confidence: 82%
“…Childbearing is considered to have great importance in most parts of Africa and being motherhood elevated social status [21][22][23]. In this study of 397 women of reproductive age, ART users in Gondar city administration have participated, we found that the proportion of fertility desire was 55.2%( 95%CI, 50.4, 60.2).Our finding in line with the fertility desire reported in Addis Ababa (54.6%) and…”
Section: Discussionsupporting
confidence: 82%
“…Factors frequently associated with risky sexual practices were sociodemographics, fertility related, ART related and partner related conditions. 16,17,[20][21][22] Many studies show a high incidence of STI during ART treatment 14,18,[23][24][25][26] and continued fertility desire among those living with HIV, [27][28][29][30][31] both suggesting the aspiration for and practice of unprotected sex. Ethiopia is primarily focusing on people uninfected with HIV and the sexual risk practices of HIV infected individuals did not receive due attention.…”
Section: Introductionmentioning
confidence: 99%
“…This may also explain the persistently high fertility observed in Malawi . Studies from Uganda and Kenya also reported that early resumption of sexual activity after delivery and fertility desires were associated with social, demographic, and societal factors …”
Section: Discussionmentioning
confidence: 99%